Incidencias de Brucella ovis del hato ganadero ovino de la carrera de medicina veterinaria de la Universidad Técnica de Babahoyo - Galarza Varas, Jorge Tomas (2024)
Ovine brucellosis, caused by Brucella ovis, is an infectious disease that can have negative impacts on the health of sheep. This study, carried out at the Technical University of Babahoyo in the Veterinary Medicine program, aimed to evaluate the incidence of Brucella ovis in the university's sheep herd. With an evaluative and descriptive methodology, where the results obtained on the presence of Brucella ovis in the herd will be evaluated, using the Rose Bengal serological test, blood samples from the 31 animals in the herd were analyzed. The results were all negative, indicating a total absence of the disease in the animals studied. These findings suggest that the management practices and sanitary measures implemented at the university are effective in keeping the herd free of Brucella ovis. However, it is recommended to continue with periodic monitoring and maintain strict biosafety measures to prevent possible future introductions of the disease. Likewise, it is advisable to carry out more studies on sheep every 6 months to identify possible outbreaks when introducing more cattle to the sheep herd, and to improve control strategies. Finally, it is essential to notify the authorities of the veterinary medicine career for adequate control and prevention of this disease.